Management of Teaching Material Development Competency-Based to Increase Life Skill Vocational High School Students - Nurjaman, Ujang; Sujiarto, Heru; Khoeriyah, N. Dede; Khori, Ahmad (Universitas Pendidikan Indonesia, 2021)
This study aims to determine the competency-based teaching materials development program to improve student life skills, implementation, problems and challenges, and future improvement steps. The method used in this research is descriptive qualitative. This research was conducted at the Ma'arif Nahdotul Ulama Vocational High School, Garut Regency, West Java Province. The data collection techniques were interviews and documentation, while the data analysis techniques used were qualitative data analysis techniques using an inductive approach. The research results are: First, the teaching material development program carried out is planning development quality objectives, establishing a School Activity Plan, collaborating with the business world and the industrial world. Second, the implementation is that the partnership relationship is not optimal. Implementing the guidelines for the development of teaching materials is not optimal. Good management is needed in implementing the results of the development of teaching materials, and an additional budget is required. Third, the problems faced are poor management of school principals, inadequate curriculum development and cooperation, preliminary school budgets, a productive syllabus that needs to be developed, and industrial practices for production are not optimal. Simultaneously, the future challenges are the student resources managing the partnership, the students' character, and the demands for practical facilities that require special attention. Fourth, the corrective steps are that the regulation of material development needs particular attention, additional budget is needed, the apprenticeship material must adjust to the productive syllabus, quality learning, improved competency tests, the competence of educators needs to be improved, optimizing the acceptance of new students, completing facilities and infrastructure.